Evaluate the diameter of the pizza box, Mathematics

If the area of a small size pizza is 78.5 in2, what size pizza box would required for the small pizza? (Note: Pizza boxes are calculated according to the length of one side.)

a. 12 in

b. 11 in

c. 9 in

d. 10 in

d. The area of a small pizza is 78.5 in2. The question requires us to evaluate the diameter of the pizza in order to choose the most appropriate box. Area is similar to πr2. Thus, 78.5 = πr2; divide by π (3.14); 78.5 ÷ 3.14 = πr2 ÷ 3.14; 25 = r2; 5 = r. The diameter is twice the radius or 10 inches. Thus, the box is also 10 inches.

Posted Date: 5/23/2013 6:25:48 AM | Location : United States

Related Discussions:- Evaluate the diameter of the pizza box, Assignment Help, Ask Question on Evaluate the diameter of the pizza box, Get Answer, Expert's Help, Evaluate the diameter of the pizza box Discussions

Write discussion on Evaluate the diameter of the pizza box
Your posts are moderated
Related Questions
What is Substitution Technique of Linear Equations?

my daughter in kg now how can i train her to develop skills in undertanding the basics of all subjects how can i start teaching other than schol

Determine the solution to the subsequent differential equation. dv/dt = 9.8 - 0.196v Solution Initially we require finding out the differential equation in the accurate

Now we start solving constant linear, coefficient and second order differential and homogeneous equations. Thus, let's recap how we do this from the previous section. We start alon

if a+1/b=b+1/c=c+1/a then the value of abc is

(a) Determine the matrix that first rotates a two-dimensional vector 180° anticlockwise, and then per- forms a horizontal compression of the resulting vector by a factor 1/2 (leavi

solve the differential equation 8yk+2-6yk+1+yk=9 ,k=0 given that Y0=1 and y1=3/2

In the diagram points V,W,X,Y and Z are collinear, VZ=52, XZ= 20 AND WX=XY=YZ. Find the indicated length of WX, VW, WY, VX, WZ, and VY

Prove: 1/cos2A+sin2A/cos2A=sinA+cosA/cosA-sinA

In this part we look at another method to obtain the factors of an expression. In the above you have seen that x 2 - 4x + 4 = (x - 2) 2 or (x - 2)(x - 2). If yo